2012
DOI: 10.1111/j.1540-8175.2012.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antithyroid Treatment on Atrial Conduction Times in Patients with Subclinical Hyperthyroidism

Abstract: SH is associated with prolonged atrial conduction time. After achievement of euthyroid state, decrement in atrial conduction time may reveal how the antithyroid treatment may prevent the development of atrial fibrillation in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
2
9
1
2
Order By: Relevance
“…[31][32][33] However, we did not find any differences in terms of LA size and LA voltage between patients with history of hyperthyroidism and those without. Nevertheless, we demonstrated that the mean RA voltage was significantly lower in patients with history of hyperthyroidism.…”
Section: Hyperthyroidism and Non-pvs Triggerscontrasting
confidence: 68%
“…[31][32][33] However, we did not find any differences in terms of LA size and LA voltage between patients with history of hyperthyroidism and those without. Nevertheless, we demonstrated that the mean RA voltage was significantly lower in patients with history of hyperthyroidism.…”
Section: Hyperthyroidism and Non-pvs Triggerscontrasting
confidence: 68%
“…Abnormal rhythms, particularly atrial fibrillation but also flutter and paroxysmal tachycardia, occur commonly in patients with ASD. 11,16,17 In our study, we found that both intra-atrial and inter-AEMCT were not prolonged in patients with ASD than control subjects. 3 In various reports, arrhythmias have been noted in about 15-50% of patients beyond the age of 20 years; the incidence increases with advancing age.…”
Section: Discussionsupporting
confidence: 43%
“…There are scarce data about the effects of hyperthyroidism on atrial electromechanical duration in the literature. Nacar et al . reported that subclinical hyperthyroidism was associated with prolonged atrial conduction time that might be improved by achievement of euthyroid state.…”
Section: Discussionmentioning
confidence: 99%